Social and professional skills of adolescents with autism spectrum disorders - Ostrovska, Kateryna; Ostrovskii, Ihor; Korniat, Vira (Special Education, 2018)
The article deals with investigation of professional skills of adolescents with autism spectrum disorders (ASD). 40 ukrainian adolescents of 13-17 years old were investigated by use of Psychological and Educational Profile for Youth and Adult (AAPEP). Besides 40 healthy peers were investigated by the same method and used as a reference group. According the results obtained 40% of ASD adolescents have satisfactory professional skills. Nevertheless, their emotional indices were substantially lower than correspondent indices for healthy peers and showed negative dynamics with age. Low indices of emotional development and functional communication skill of ASD adolescents restrict their future employment and demond psychological and social support.
Keywords: autism spectrum disorders; adolescents; professional skill; social competence